Students’ feedback about “Physiotherapy of orthopaedic diseases” with full-time online teaching - Zhang, Ruike; Huang, Tao; Wen, Yanping; Zhang, Zhuopeng; Shi, Kai; Wu, Yuan (Journal of the Pakistan Medical Association, 2025)
Objectives: To evaluate the perceptions of physiotherapy students regarding the effectiveness of full-time online teaching in the Physiotherapy of Orthopaedic Diseases course, focusing on satisfaction levels, theoretical knowledge acquisition, and practical skill development during the later stage of the coronavirus disease-2019 pandemic. Method: The mixed-methods study was conducted at the Fifth Clinical College of Guangzhou Medical University, China, from October 2022 to January 2023, and comprised students from the 2020 cohort of the four-year physiotherapy major who had attended the Physiotherapy of Orthopaedic Diseases course from September 2022 to January 2023. Quantitative data was collected through pre- and post-online course surveys. Qualitative data was gathered through semi-structured interviews. Quantitative data was analysed using SPSS 25, while qualitative data was subjected to thematic analysis. Results: Of the 61 subjects with mean age 21.41 ± 0.72, 40(65.6%) were females and 21(34.4%) were males. Post-course ratings score 13.77±4.03 showed a significant decline in satisfaction with the course and teaching effectiveness compared to pre-course ratings 15.28±2.65(p=0.02). While sharing qualitative insights, the students appreciated instructors’ enthusiasm, but expressed concerns about the absence of practical online activities and direct interaction essential for physiotherapy skill development. However, online practical sessions provided a conducive environment for skill demonstration, and fostered student-teacher engagement. Conclusion: Well-designed online educational methods are necessary that are tailored to the practical demands of physiotherapy education. Strategic enhancements are essential to bridging the gap in practical skills training through online teaching. Key Words: Distance education, Student satisfaction, Educational methods, Practical skills, Educational technology.